SHAPING THE CHILDREN’S SOCIAL CARING CHARACTERS THROUGH GOBAK SODOR GAME - Imro’atul Khoiriyah; Erik Aditia Ismaya; Deka Setiawan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the behavior of children aged 6–12 years and to analyze the children’s behavior towards social care character values through playing gobak sodor. The type of this study was qualitative descriptive which involved children aged 6–12 years with low social awareness as the research subjects. Data were collected through observation and interviews. Then, the data were analyzed by using the interactive model analysis technique from Miles and Huberman (data reduction, data presentation, drawing conclusions). The validity was examined by technique and source triangulation. Social care was a behavior or action carried out by individuals consciously towards other individuals so as to create interactions with the wider community. In social life, especially in heterogeneous communities, social care was required by individuals (children). Social care would become learning when interacting with other children. Every interaction trained children to have high social sensitivity towards friends and their environment. Social care for children could be applied through a traditional Indonesian game known as Gobak Sodor. The results showed that there was an increase in the character of social care after playing the traditional game Gobak Sodor. Social attitudes that were very striking were the attitude of responsibility, focus, and tolerance.